You are on page 1of 5

Homework 5 Solutions

Problem 1
For a system defined by:
𝑀𝑥̈ + 𝐾𝑥 = 0
To find the natural frequencies and mode shapes, we need to solve an eigenvalue problem:

𝑀−1 𝐾 − 𝜔2 𝐼 = 0
Let:

𝐴 = 𝑀−1 𝐾, 𝜆 = 𝜔2
We are going to find the eigenvalues 𝜆𝑖 and eigenvector 𝑣𝑖 of matrix A.
3.6 1.2 0.2
𝐴 = 𝑀−1 𝐾 = [ 1 1.5 −1.667]
0.125 −1.25 2.5
Calculating the determinant gives:
3.6 − 𝜆 1.2 0.2 38 1781 197
|𝐴 − 𝜆𝐼| = | 1 1.5 − 𝜆 −1.667| = −𝜆3 + 𝜆2 − 𝜆+ =0
5 120 80
0.125 −1.25 2.5 − 𝜆
Solving this equation gives:
𝜆1 = 0.1826, 𝜆2 = 3.1919, 𝜆3 = 4.2256
Which leads to:
𝜔1 = 0.4273, 𝜔2 = 1.7866, 𝜔3 = 2.0556
To find the eigenvector 𝑣𝑖 corresponding to eigenvalues 𝜆𝑖 , plug 𝜆𝑖 into the following equation and solve
for 𝑣𝑖 :
[𝐴 − 𝜆𝑖 𝐼]𝑣𝑖 = 0
End up with normalized eigenvectors:
0.3176 0.6232 −0.8288
𝑣1 = [−0.8273] , 𝑣2 = [−0.3301] , 𝑣3 = [ −0.48 ]
−0.4634 0.7090 0.2877

In Matlab, we can use function ‘eig’ to verify the solution.

(Students should show the steps to solve this problem. It’s OK to have flipped +/− sign on eigenvectors.)
Problem 2
Part (a)

The matrices 𝐴10 , 𝐴12 , 𝐴23 , 𝐴34 are of the form:

𝐴 = [𝑅 𝑃𝑇 ]
0 1
Thus, the expression of 𝐴10 , 𝐴12 , 𝐴23 , 𝐴34 are as follows where 𝑐𝜃 = cos 𝜃 and 𝑠𝜃 = sin 𝜃
𝑐𝜃1 −𝑠𝜃1 𝐿1 𝑐𝜃1
𝐴10 = [𝑠𝜃1 𝑐𝜃1 𝐿1 𝑠𝜃1 ]
0 0 1
1 0 𝑑2∗
𝐴12 = [0 1 0]
0 0 1
𝑐𝜃3∗ −𝑠𝜃3∗ 𝐿3 𝑐𝜃3∗
𝐴23 = [𝑠𝜃3∗ 𝑐𝜃3∗ 𝐿3 𝑠𝜃3∗ ]
0 0 1
𝑐𝜃4∗ −𝑠𝜃4∗ 𝐿4 𝑐𝜃4∗
𝐴34 = [𝑠𝜃4∗ 𝑐𝜃4∗ 𝐿4 𝑠𝜃4∗ ]
0 0 1

Part (b)
𝑇40 = 𝐴10 𝐴12 𝐴23 𝐴34
𝑐(𝜃1 + 𝜃3∗ + 𝜃4∗ ) −𝑠(𝜃1 + 𝜃3∗ + 𝜃4∗ ) 𝐿1 𝑐𝜃1 + 𝑑2∗ 𝑐𝜃1 + 𝐿3 𝑐(𝜃1 + 𝜃3∗ ) + 𝐿4 𝑐(𝜃1 + 𝜃3∗ + 𝜃4∗ )
= [𝑠(𝜃1 + 𝜃3∗ + 𝜃4∗ ) 𝑐(𝜃1 + 𝜃3∗ + 𝜃4∗ ) 𝐿1 𝑠𝜃1 + 𝑑2∗ 𝑠𝜃1 + 𝐿3 𝑠(𝜃1 + 𝜃3∗ ) + 𝐿4 𝑠(𝜃1 + 𝜃3∗ + 𝜃4∗ )]
0 0 1

Part (c)
𝑇40 is a description of the position and orientation of the coordinate-frame attached to the end-
effector relative to the base-frame. Thus, the expressions for position are equivalent to the entries
corresponding to 𝑃𝑇 of the matrix 𝑇40
𝑋𝑝𝑜𝑠 𝐿 𝑐𝜃 + 𝑑2∗ 𝑐𝜃1 + 𝐿3 𝑐(𝜃1 + 𝜃3∗ ) + 𝐿4 𝑐(𝜃1 + 𝜃3∗ + 𝜃4∗ )
𝑃𝑇 = [ ]=[ 1 1 ]
𝑌𝑝𝑜𝑠 𝐿1 𝑠𝜃1 + 𝑑2∗ 𝑠𝜃1 + 𝐿3 𝑠(𝜃1 + 𝜃3∗ ) + 𝐿4 𝑠(𝜃1 + 𝜃3∗ + 𝜃4∗ )

Part (d)
Plug the values into the equation found in part (c). This gives us the position of the tool-frame:
𝑋𝑝𝑜𝑠 4.5336
𝑃𝑇 = [ ]=[ ]
𝑌𝑝𝑜𝑠 12.1955

In the 2D plane, the orientation of the tool-frame is simply the summation of the rotations.
𝜋 𝜋 5𝜋 25𝜋 1𝜋
𝜃𝑡 = 𝜃1 + 𝜃3∗ + 𝜃4∗ = + + = , 𝑜𝑟
3 2 4 12 12

Part (e)
0.9659 −0.2588 4.5336 2 6.2066
0 4
𝑃𝑡𝑜𝑜𝑙 = 𝑇40 ∗ 𝑃𝑡𝑜𝑜𝑙 = [0.2588 0.9659 12.1955] [1] = [13.6791]
0 0 1 1 1

So, the tool end point in base frame is


0 6.2066
𝑃𝑡𝑜𝑜𝑙 =[ ]
13.6791

Problem 3
Part (a)
There are two solutions.

Part (b)
We are trying to solve this problem in frame 2. We need to find the representation of the desired
point [𝑥3 , 𝑦3 ]𝑇 in frame 2, and the representation of the origin of frame 3 in frame 2.
Represent point [𝑥3 , 𝑦3 ]𝑇 in frame 2.
𝑐𝜃1 −𝑠𝜃1 𝐿1 𝑐𝜃1 + 𝑑2∗ 𝑐𝜃1
𝑇20 = 𝐴1 𝐴2 = [𝑠𝜃1 𝑐𝜃1 𝐿1 𝑠𝜃1 + 𝑑2∗ 𝑠𝜃1 ]
0 0 1
Find the inverse of this homogeneous transformation
𝑐𝜃 𝑠𝜃1 −𝐿1 − 𝑑2∗
𝑇02 = [𝑅
−1
−𝑅 −1 𝑃] = [ 1 ]
−𝑠𝜃1 𝑐𝜃1 0
0 1
0 0 1
Then
𝑐𝜃1 𝑠𝜃1 −𝐿1 − 𝑑2∗ 𝑥3 −𝐿1 − 𝑑2∗ + 𝑥3 𝑐𝜃1 + 𝑦3 𝑠𝜃1
𝜌32 = 𝑇02 ∗ 𝜌30 = [−𝑠𝜃1 𝑐𝜃1 0 ] [𝑦3 ] = [ −𝑥3 𝑠𝜃1 + 𝑦3 𝑐𝜃1 ]
0 0 1 1 1

Represent the origin of frame 3in frame 2.


𝑐𝜃3∗ −𝑠𝜃3∗ 𝐿3 𝑐𝜃3∗
𝑇32 = 𝐴3 = 𝐴23 = [𝑠𝜃3∗ 𝑐𝜃3∗ 𝐿3 𝑠𝜃3∗ ]
0 0 1
Then
𝐿3 𝑐𝜃3∗
𝑃32 = [𝐿3 𝑠𝜃3∗ ]
1
Thus, we get two equations
𝐿3 𝑐𝜃3∗ = −𝐿1 − 𝑑2∗ + 𝑥3 𝑐𝜃1 + 𝑦3 𝑠𝜃1
𝐿3 𝑠𝜃3∗ = −𝑥3 𝑠𝜃1 + 𝑦3 𝑐𝜃1
What remains to do is to solve (𝑑2∗ , 𝜃3∗ ) out from the two equations above.
𝐿23 = (−𝐿1 − 𝑑2∗ + 𝑥3 𝑐𝜃1 + 𝑦3 𝑠𝜃1 )2 + (−𝑥3 𝑠𝜃1 + 𝑦3 𝑐𝜃1 )2
−𝑥3 𝑠𝜃1 + 𝑦3 𝑐𝜃1
tan 𝜃3∗ =
−𝐿1 − 𝑑2∗ + 𝑥3 𝑐𝜃1 + 𝑦3 𝑠𝜃1
It gives us two solution for 𝑑2∗
Situation 1:

𝑑2∗ = −𝐿1 + 𝑥3 𝑐𝜃1 + 𝑦3 𝑠𝜃1 − √𝐿23 − (−𝑥3 𝑠𝜃1 + 𝑦3 𝑐𝜃1 )2

−𝑥3 𝑠𝜃1 + 𝑦3 𝑐𝜃1


𝜃3∗ = tan−1 = 𝑎𝑡𝑎𝑛2(−𝑥3 𝑠𝜃1 + 𝑦3 𝑐𝜃1 , √𝐿23 − (−𝑥3 𝑠𝜃1 + 𝑦3 𝑐𝜃1 )2 )
√𝐿23 − (−𝑥3 𝑠𝜃1 + 𝑦3 𝑐𝜃1 )2
Situation 2:

𝑑2∗ = −𝐿1 + 𝑥3 𝑐𝜃1 + 𝑦3 𝑠𝜃1 + √𝐿23 − (−𝑥3 𝑠𝜃1 + 𝑦3 𝑐𝜃1 )2

−𝑥3 𝑠𝜃1 + 𝑦3 𝑐𝜃1


𝜃3∗ = tan−1
−√𝐿23 − (−𝑥3 𝑠𝜃1 + 𝑦3 𝑐𝜃1 )2

= 𝑎𝑡𝑎𝑛2(−𝑥3 𝑠𝜃1 + 𝑦3 𝑐𝜃1 , −√𝐿23 − (−𝑥3 𝑠𝜃1 + 𝑦3 𝑐𝜃1 )2 )

atan2(y,x) is a function used in engineering and computer science to return the correct
angle/quadrant for values of y and x.

Part (c)
Since
𝜃𝑡 = 𝜃1 + 𝜃3∗ + 𝜃4∗
We have
𝜃4∗ = 𝜃𝑡 − 𝜃1 − 𝜃3∗
Plug in 𝜃3∗ we get from part (b) to get the equation for 𝜃4∗

You might also like